Promotional Language of the Local and International Brands of Halal Food Products: A Comparative Analysis - Wan Mohd Fadzlullah, Wan Nor Fasihah; Ariffin, Adlina (2019)
The growing popularity of halal products around the world has opened up the market segment with an abundance of potential. On Malaysia’s road to being a global halal hub by 2020, the mechanics of marketing halal food has been identified as one of the significant contributing factors. Hence, this paper will highlight the linguistic elements utilized in the promotional discourse of halal food that is found in local and international product print advertisements. This corpus-based analysis research looks into the textual and visual content of the advertisements as part of the promotional language. The research presents an analysis of one hundred printed promotional materials of halal food which were collected from several halal food events and exhibitions in the Klang Valley. The finding calls to attention of the important elements that are found in the promotional language strategies employed by marketers of halal food in both local and international brands. By marketing ‘halal’ and its concepts such as ‘healthy’, ‘safe’ and ‘clean’ as the main idea, this will cater for the Muslim consumers’ needs in observing halalan toyyiban’ (halal and good) in their life and would undoubtedly benefit other consumers as well. This shows the significance of applying suitable linguistic elements to deliver the halal message whilst achieving specific marketing goals, and for Malaysia to ultimately lead the global halal food industry.